2017
DOI: 10.1038/s41598-017-11464-x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-derived host defence peptide modulates neutrophil rolling and migration in vitro and functional response in vivo

Abstract: Host defence peptides (HDPs) derived from the C-terminus of thrombin are proteolytically generated by enzymes released during inflammation and wounding. In this work, we studied the effects of the prototypic peptide GKY25 (GKYGFYTHVFRLKKWIQKVIDQFGE), on neutrophil functions. In vitro, GKY25 was shown to decrease LPS-induced neutrophil activation. In addition, the peptide induced CD62L shedding on neutrophils without inducing their activation. Correspondingly, GKY25-treated neutrophils showed reduced attachment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…This interference with TLR signaling provides a molecular explanation for the previously observed therapeutic effects of TCP-25 in experimental models of bacterial sepsis and endotoxin shock (27,32,33). In addition, the peptide reduces inflammatory responses to intact bacteria during phagocytosis (34) and inhibits neutrophil responses to LPS in vitro and in vivo (35).…”
Section: Introductionmentioning
confidence: 81%
“…This interference with TLR signaling provides a molecular explanation for the previously observed therapeutic effects of TCP-25 in experimental models of bacterial sepsis and endotoxin shock (27,32,33). In addition, the peptide reduces inflammatory responses to intact bacteria during phagocytosis (34) and inhibits neutrophil responses to LPS in vitro and in vivo (35).…”
Section: Introductionmentioning
confidence: 81%
“…Injury and infection are serious threats to the survival of an organism, and nature has therefore evolved powerful natural peptidebased mechanisms for controlling excessive bacterially-induced inflammation. Peptides derived from the C-terminus of thrombin (TCPs), initially discovered in human wounds 14 , control both bacterial infections and the associated inflammatory responses [15][16][17] via transient and multiple interactions with Gram-positive and negative-bacteria and their PAMPs, and subsequent interference with CD14-mediated TLR signaling [15][16][17] , neutrophil chemotaxis 18 , and excessive contact activation 17 .…”
mentioning
confidence: 99%
“…Also thrombin released various active peptides (Papareddy et al 2010). It was indeed demonstrated that the thrombin derived hostdefense peptide GKY25 (GKYGFYTHVFRLKKWIQKVIDQFGE) deriving from the C-terminus of the protein inhibited LPS-induced responses of monocytes, macrophages, and neutrophils in vitro, ex vivo, and in vivo (Singh et al 2013;Hansen et al 2015;Lim et al 2017). GKY25 showed a broad and inhibitory effect on multiple sepsis pathologies.…”
Section: Miscellaneous Cryptidesmentioning
confidence: 99%